Isolation, Structural Elucidation, Optical Resolution, and Antineuroinflammatory Activity of Phenanthrene and 9,10-Dihydrophenanthrene Derivatives from Bletilla striata - Zhou, Di; Chen, Gang; Ma, Yue-Ping; Wang, Cun-Gang; Lin, Bin; Yang, Yan-Qiu; Li, Wei; Koike, Kazuo; Hou, Yue; Li, Ning (Journal of natural products (Washington, D.C.), 2019)
A phytochemical investigation of the aqueous EtOH extract of Bletilla striata tubers afforded 34 phenanthrene and 9,10-dihydrophenanthrene derivatives, including four new compounds, 1–4. These compounds were identified using physicochemical analyses and various spectroscopic methods. Twelve of these compounds were resolved into their enantiomers, and the absolute configurations were determined by comparison of experimental and calculated ECD spectra. The antineuroinflammatory activities were evaluated by measuring the inhibition of nitric oxide production in lipopolysaccharide-stimulated BV-2 microglial cells. Compounds 7, 32, and 33 displayed inhibitory activities, with IC50 values of 1.9, 5.0, and 1.0 μM, respectively, suggesting that they should be subjected to development as potential inhibitors of neuroinflammation.